Respuesta :
Answer:
The average velocities are:
for 0.01.s
- [tex]<v> = - 68.19 \frac{ft}{s} \hat{j}[/tex]
for 0.005 s
- [tex]<v> = - 68.2 \frac{ft}{s} \hat{j} [/tex]
for 0.002 s
- [tex]<v> = - 68.05 \frac{ft}{s} \hat{j} [/tex]
for 0.001 s
- [tex]<v> = - 68.02 \frac{ft}{s} \hat{j}[/tex]
Explanation:
The average velocity is given by
[tex]<v> = \frac{displacement}{time}[/tex]
So, we just need to find the position at t = 3 s and then, after every period of time.
Position at t = 3 s
Knowing that
[tex]y(t) = 46 \frac{ft}{s} t - 19 \frac{ft}{s^2} \ t^2[/tex]
at t = 3 s we have
[tex]y(3 \ s) = 46 \frac{ft}{s} * 3 s - 19 \frac{ft}{s^2} * (3 \ s)^2[/tex]
[tex]y(3 \ s) = 138 ft - 19\frac{ft}{s^2} * 9 \ s^2[/tex]
[tex]y(3 \ s) = -33 ft[/tex]
After 0.01 s
After 0.01 s the position will be
[tex]y(3.01 s) = 46 \frac{ft}{s} 3.01 s - 19 \frac{ft}{s^2} \ (3.01 s)^2[/tex]
[tex]y(3.01 s) = -33.6819 ft[/tex]
So, the average velocity will be
[tex]<v> = \frac{-33.6819 ft \hat{j}- (-33 ft) \hat{j}}{0.01 s}[/tex]
[tex]<v> = \frac{-0.6819 ft \hat{j}}{0.01 s}[/tex]
[tex]<v> = - 68.19 \frac{ft}{s} \hat{j}[/tex]
The minus sign is there cause the velocity is pointing downward.
After 0.005 s
After 0.005 s the position will be
[tex]y(3.005 s) = 46 \frac{ft}{s} 3.005 s - 19 \frac{ft}{s^2} \ (3.005 s)^2[/tex]
[tex]y(3.005 s) = -33.3405 ft[/tex]
So, the average velocity will be
[tex]<v> = \frac{-33.3405 ft \hat{j} - (-33 ft) \hat{j} }{0.005 s}[/tex]
[tex]<v> = \frac{-0.3405 ft }{0.005 s} \hat{j}[/tex]
[tex]<v> = - 68.2 \frac{ft}{s} \hat{j}[/tex]
After 0.002 s
After 0.002 s the position will be
[tex]y(3.002 s) = 46 \frac{ft}{s} 3.002 s - 19 \frac{ft}{s^2} \ (3.002 s)^2[/tex]
[tex]y(3.002 s) = -33.1361 ft[/tex]
So, the average velocity will be
[tex]<v> = \frac{-33.1361 ft \hat{j} - (-33 ft) \hat{j} }{0.002 s}[/tex]
[tex]<v> = \frac{-0.1361 ft \hat{j} }{0.002 s}[/tex]
[tex]<v> = - 68.05 \frac{ft}{s} \hat{j} [/tex]
After 0.001 s
After 0.001 s the position will be
[tex]y(3.001 s) = 46 \frac{ft}{s} 3.001 s - 19 \frac{ft}{s^2} \ (3.001 s)^2[/tex]
[tex]y(3.001 s) = -33.06802 ft[/tex]
So, the average velocity will be
[tex]<v> = \frac{-33.06802 ft \hat{j} - (-33) ft \hat{j} }{0.001 s}[/tex]
[tex]<v> = \frac{-0.06802 ft \hat{j} }{0.001 s}[/tex]
[tex]<v> = - 68.02 \frac{ft}{s} \hat{j}[/tex]